Patrani - Mitra, Vimal (India : Penguin, 2020)
This is a struggled story of a woman. How could a fatherless girl born in the gutter grow up to be the beauty of the royal place struggling on the strength of hatred and ambition in her heart. It is well shown in it. She keeps helping her brother and sister even after going to the palace. Looks at them not with love, but with hatred and hate themselves that they are poor and why did I become rich?
Keywords: Story